Paid Plastic Shopping Bags Policy: What the Factors Drive the Implementation? - Yudiatmaja, Wayu Eko; Solina, Emmy; Prastya, Imam Yudhi; Yudithia, Yudithia; Samnuzulsari, Tri (Journal of Governance and Public Policy, 2022)
Several regional governments in Indonesia have implemented paid plastic shopping bags policy to reduce micro-plastic waste. However, there are only a few studies to evaluate this program. To fill the research gap, the researchers seek to implement the regulation by investigating policy effectiveness factors. The ultimate purpose of this paper is to illuminate what factors affect the policy. The researchers studied the implementation of paid plastic bags in Depok City, West Java, Indonesia, by employing a survey to achieve the objective. One hundred and thirty-four respondents had participated in this research and shared their responses on the policy. A partial least square structural equation modeling (PLS-SEM) was applied to analyze the data. The results showed three factors contributed to policy implementation: knowledge, awareness, and compliance. The current research extends Grindle’s theory by examining individual determinants as predictors of policy implementation. This study also adds the researchers’ knowledge into how society responds to Indonesia’s paid plastic shopping bags policy and contributes to the government designing a suitable strategy to implement the program effectively.